Antibody level against COVID-19 among the vaccinated infected and non-infected doctors by SARS-COV-2: A Comparative study - Nazma Akhter; Forhadul Hoque Mollah; Nowrose Jahan; Jurdi Adam; Md Arif Hossain; Md Zaforullah Chowdhury (Update Dental College, 2022)
Introduction: A novel coronavirus (2019-nCoV or SARS-CoV-2) emerged at the end of 2019 in Wuhan, Hubei province, China named as COVID-19. IgM, the first antibody produced by the body, is generated gradually 1 week after symptom onset and declines by 4 weeks after the COVID infection. In this background, the antibody response was observed in vaccinated (by Oxford-AstraZeneca) doctors of SSMC(Sir Salimullah Medical College) with or without previous COVID-19 infection. Methodology: This cross-sectional analytical study was conducted in the Department of Biochemistry and Molecular Biology at SSMC and BSMMU. A total of 70 doctors of SSMC aged 25-59 years were enrolled according to inclusion criteria. Among them 35 vaccinated doctors were previously infected by SARS-CoV-2 regarded as group A and another vaccinated 35 doctors were non-infected regarded as group B. Collected data was analyzed by Statistical Package for Social Science 26 (SPSS 26). The data were expressed as frequency and percentage, mean ± SD for normally distributed data or median (inter-quartile rage) for data not normally distributed. Mann-Whitney test was done to compare IgG status between vaccinated SARS-CoV-2 infected and non-infected individuals. Result: There was significantly higher level of antibodies (serum IgG level) present in fully vaccinated doctors with previous SARS-CoV-2 infection than in only vaccinated doctors without prior infection. Update Dent. Coll. j: 2022; 12(2): 19-23